Category of Authorship Development: from Shakespeare to Romanticism - I. V. Peshkov (Научный диалог)
The subject of the research is hidden in the long work of cultural mechanisms origin and development of category of authorship. It is shown that this category gradually singled out from a triad playwright - actors - audience in the Golden age of English literature with the parallel development of dyad writer - readers . According to the author, this dyad began to strengthen with the advent of book printing, which, together with the theatre, led to the formation of a mass readership. The concept is provided, according to which the process of the category of authorship formation can be seen in W. Shakespeare, the genius author. It is suggested that one can speak about the first stage of approval of the “author” category in connection with the publication of the First folio in 1623. It is emphasized that the final transfiguration of W. Shakespeare in the author-creator was only by the end of the 18th century - early 19th century, when the English and German romantics turned to the concept of genius developed by I. Kant. It is argued that romanticism intuitively appreciated Kant’s creative imagination as a distinctive feature of Shakespeare’s works, and it came to the conclusion that the ability to imagine and to build a new world considers the subject of this ability as the chief creative component. Review of works of the 18th century showed that English philologists have also contributed to the development of the category of authorship. So, E. Young was one of the first who clearly distinguished between imitators and the original authors. It is proved that the idea of originality developed in the romanticism to the idea of the poet as prophet, original and genius to such an extent that his time is not able to recognize him, and therefore, he will be completely appreciated only by future generations.